Pemanfaatan Larutan Ulang Asap Cair Terhadap Mutu Ikan Selais (Cryptopterus bicirchis) Asap - Noviana Chasmayani; Desmelati Desmelati; Sumarto Sumarto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
This research was conducted at the laboratory of Fish Processing Technology, Faculty of fisheries and Marine Science, University of Riau, on January 2014. The research was intended to evaluate the effect of liquid smoke solution which used repeatedly to the smoked catfish (Cryptopterus bicirchis) quality. Liquid smoke which was made from condensate of scull was prepared. The fish was soaked on 80 ml of liquid smoke solution for 30 minutes. Four types of smoked catfish were soaked on 80 ml of liquid smoke solution for 30 minutes repeatedly, and then the smoked catfish was stored in oven for 10 hours. Smoke catfish was evaluated for sensory quality, mositure, pH, acidity and fenol. The result showed that the first soaking of smoked catfish was the best treatment. Sensory quality, moisture, pH, acidity and fenol of smoke catfish was 7,50; 20,01%; 5,87; 2,73% and 5,25% respectively.